Modular-competence approach to the professional training of the would- be skilled workers in the construction and machine building industry spheres - Yagupov, Vasyl (Professional Pedagogics, 2014)
The article proposes pedagogical rules of implementation of the modular-competence approach in the professional training of the would-be skilled workers in the construction and machine building industry spheres. It shows interrelation and mutual complementation of the modular and competence approaches principles. It highlights that these pedagogical rules have intersubjectal, integral, dynamic, multivectoral, multifunctional and, simultaneously, subjective nature. It analyzes and defines pedagogical rules of implementation of the modular-competence approach to the professional training of the would-be skilled workers in the construction and machine building industry spheres as a combination of homogeneous demands which transform into the following principles: evaluative and motivational filling of the future specialty; practical and subjective orientation of the would-be specialist’s professional training; concreteness and, simultaneously, multilateral orientation of its professional training; modeling and standardization of the would-be specialist’s professional training; providing objective support for the diagnosis of its outcome; modularity; highlighting outstanding elements in the learning content; dynamism; effectiveness and timeliness of the knowledge and its ability to function as a system; flexibility; conscious perspective; versatility of the methodical consultation; parity; complex, integral and single goals; implementation of the feedback; providing unity for the professional knowledge and skills; optimal transmission of the information and resource materials; target orientation of the informational material; support based on mistakes. The article analyzes each principle and presents its pedagogical demands.